Сезонные изменения и возрастные особенности эколого-физиологических показателей серой полевки левобережной Лесостепи Украины - Шевченко, Н.Т.; Семенченко, В.М.; Заец, А.И.; Живило, Л.И. (Вестник зоологии, 1973)
Erythrocyte number, haemoglobine concentration in blood, oxygen consumption intensity. and some morpho-physiological indicators of Microtus arvalis P a l l. were studied. Age and seasonal changes in these indices as well as difference of some of them in males and females are determined.